Sexual practices in peruvian gestants - Munares-García, Oscar (2019)
Objective. Identify sexual practices during pregnancy. Methods. Prospective, cross-sectional study conducted in 110 pregnant women attended at the La Tinguiña Health Center, Ica. A validated questionnaire was applied, which evaluated sexual practices. Subsequently, descriptive statistics were applied. Results. 69,1% were between 20 and 34 years old. 47,3% considered that their sexual life during pregnancy was regular. In the first quarter 100% indicated having preliminary games most of the time, for the second quarter it reached 59,2% and for the third quarter it reached 58,9%. The sexual frequency is reduced for those who had more times per week, increasing to those who had every fortnight, from 12,2% for the second quarter to 39,3% for the third quarter. Conclusions. The sexual practice in pregnancy changes as the quarters increase.